AOCI: An Aspect-Oriented Component Infrastructure - Söldner, Guido; Kapitza, Rüdiger (Proceedings of the 12th International Workshop on Component Oriented Programming (WCOP 2007), 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD4.aocian

AOCI: Ontology-based Pointcuts - Söldner, Guido; Kapitza, Rüdiger; et al. (Proceedings of the 8th AOSD Workshop on Aspects, Components, and Patterns for Infrastructure Software (AOSD-ACP4IS '09), 2009)
In this paper, we propose ontology-based pointcuts, a novel mechanism based on the ideas of AOP, the separation of concerns and system modularization, to enhance components, thus making them more adaptable and evolvable. The core idea of ontologybased pointcuts is to specify pointcuts in terms of ontological concepts instead of patterns that are matched against source code. Components are usually considered as black boxes that can be combined to a complex system using their outer interfaces. In the context of our infrastructure, components are extended by exporting possible adaptation points, which are enriched by ontological information. This ontological metadata represents concepts from a domain model, defined by a domain expert. The ontology is implemented within an intermediate layer that decouples the matching pointcuts from the concrete source level within the components. This enables the application of AOP techniques without detailed knowledge about the component's internals, enabling dynamic and distributed adaptation and reducing the fragile pointcut problem to the component scope. This paper presents the design and the expressiveness of the ontology-based pointcuts. We show several practical examples how to use joinpoint model and the pointcut specification followed by a short discussion. Copyright 2009 ACM.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD4.aocion
Keywords: dynamic adaptation; metadata-driven adaptation; osgi

AOCI: Weaving Components in a Distributed Environment - Söldner, Guido; Schröder-Preikschat, Wolfgang; Kapitza, Rüdiger; et al. (On the Move to Meaningful Internet Systems 2008: CoopIS, DOA, ODBASE, GADA, and IS, 2008)
Mobile and embedded devices like PDAs, mobile phones, and all kinds of consumer hardware populate the world we live in. Despite the vision of ubiquitous computing and its idea of spontaneous interaction among these devices more than fifteen years ago, most of them are still isolated and restricted in their interaction capabilities. One reason for this limitation is the poor support for dynamic adaptation and evolution of software in distributed environments. This paper proposes AOCI, an Aspect-Oriented Component Infrastructure that takes the core ideas of AOP, the separation of concerns and system modularization to make them more adaptable and evolvable, to the domain of component systems. Components are usually considered as black boxes that can be combined to a complex system using their outer interfaces. In the context of our infrastructure, components export possible adaptation points, which are enriched by ontological information. This enables the application of AOP techniques without detailed knowledge about the component's internals, enabling dynamic and distributed adaptation. Our prototype is based on OSGi and provides a complete infrastructure to weave local as well as remote components. We demonstrate the feasibility of our approach by adapting the RUBiS infrastructure (a web-based bidding system) to support dynamic user-centric error detection. © 2008 Springer Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD4.aociwe

Dynamic Weaving of Components in a Distributed Environment - Söldner, Guido; Kapitza, Rüdiger; et al. (ACM/IFIP/USENIX 9th International Middleware Conference, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD4.dynami

Providing Context-Aware Adaptations Based on a Semantic Model - Söldner, Guido; Kapitza, Rüdiger; Meier, René (Proceedings of the 11th IFIP International Conference on Distributed Applications and Interoperable Systems, 2011)
Smartphones and tablet PCs are on the verge of revolutionizing the information society by offering high quality applications and almost permanent connectivity to the Internet in a mobile world. They naturally support new applications that take advantage of context information like location, time and other environmental conditions. However, developing these novel context-aware applications is challenging as it is difficult to a priori anticipate their execution context and the adaptations that might be necessary to use new context information. This issue is reinforced by the semantic gap between the low-level technical realization of adaptation mechanisms and the demand to describe adaptations in abstract and comprehensible business terms. This paper presents programming support for context-aware adaptations based on a semantic model that builds on the AOCI framework. Using such a model, applications and adaptations can be described by means of easy to comprehend business terms. Thereby the model enables the AOCI framework to store and publish both context and domain-specific run-time information and provides a basis for high-level and tailored programming support. This enables to transparently select adaptations based on various criteria and integrate them into applications at run-time. At the level of adaptation mechanisms our approach supports integration for permanent changes using Aspect-Oriented Programming and more importantly for spontaneous and short-time integration of web services by means of interceptors. © 2011 IFIP International Federation for Information Processing.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.provid
Keywords: AOCI

Semantische Adaption von Komponenten - Söldner, Guido (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
UnivIS-Import:2016-07-26:Pub.2012.tech.IMMD.IMMD4.semant